EFFECTS OF FENUGREEK (TRIGONELLA FOENUM-GRAECUM) SEEDS EXTRACT ON THE TESTOSTERONE AND HEMOGLOBIN LEVELS IN RABBITS - Dr. Nargis Pirya; Dr. Ghulam Mustafa Dahri; Dr. Muhammad Azhar Mughal; Dr. Zaheera Yousif Memon; Dr. Farzana Memon; Dr Aisha Asad Memon; Muhammad Zain ul Abdeen (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Fenugreek (Trigonella foenum-graecum) is known as a medicinal plant; it is used for multiple therapeutic purposes since ancient times which include hormonal and hematologic modulation. Whereas, earlier studies have explored fenugreek’s effect on the testosterone or hemoglobin concentrations alone, there is a lack of data about its pharmacological and physiological actions as dual actions. Objective: To determine the effects of the orally administered fenugreek seed extract on the serum testosterone and hemoglobin levels on adult male rabbits. Methods: A total of 30 male adult rabbits were randomized into three study groups, each group comprised of 10 rabbits. Group A was labeled as control, while Groups B and Group C received fenugreek seed extract at the doses of 500 mg/kg and 1000 mg/kg body weight respectively for a period of 45 days. Blood samples were taken periodically at the baseline, Day 23, and Day 45 to evaluate serum testosterone and hemoglobin levels. All data was analyzed by means of SPSS version 25.0, with an applied significance level of p<0.05 at Day 45. Results: Group B with a dose of 500 mg/kg of fenugreek’s seed extract, was found to have a significant increase in the serum levels of testosterone from 27.77 ± 3.27 to 29.77 ± 3.67 ng/dL (p<0.01) and also hemoglobin concentrations raised from baseline 12.06 ± 1.31 to 12.81 ± 1.23 g/dL (p<0.01) by Day 45. Group C received a dose of 1000 mg/kg of fenugreek’s seed extract, which exhibited an even greater increase in the serum testosterone levels from 26.86 ± 3.67 to 29.11 ± 3.83 ng/dL, p<0.001) and also hemoglobin raised from baseline 11.99 ± 0.97 to 12.59 ± 1.00 g/dL, p<0.001 at Day 45. In the control group, statistically no significant changes were noted. While, mild lethargy was observed in only one animal belonging to Group B; otherwise, no any side effects or mortality were observed. Conclusion: Fenugreek seed extract increases serum testosterone as well as hemoglobin levels in the adult male rabbits in a dose dependent fashion. The dual biological effects and its safety profile observed, suggest its potential use as a natural therapeutic agent in the clinical management of hypogonadism and iron-deficiency anemia.